Organizational Ethical Climate and Interpersonal Deviance: The Mediating Role of Moral Disengagement - Saidon, Intan; Galbreath, Jeremy; Whiteley, Alma (global research agency, 2012)
To understand the relationship between organizational ethical climate and interpersonal deviance in a more comprehensive way, this study suggests the mediating role of moral disengagement. Moral disengagement is a construct that explains possible keys to deactivation of an individual's self-regulatory system. Once the system is deactivated, an individual will be freed from psychological feelings of discomfort when performing deviant behavior. Data were randomly collected from 669 employees in large electrical and electronic manufacturing companies in Malaysia. Applying two-staged structural equation modeling software (Analysis of Moment Structures or AMOS}, results indicate that organizational ethical climate is negatively associated with interpersonal deviance. In addition, moral disengagement is found to mediate the relationship between organizational ethical climate and interpersonal deviance. Implications for theory and practice are discussed.